МІНІМІЗАЦІЯ НЕГАТИВНОГО ВПЛИВУ ПУСКОВИХ СТРУМІВ АСИНХРОННИХ ДВИГУНІВ НА ПАРАМЕТРИ РЕЖИМУ «СЛАБКОЇ» ЕЛЕКТРИЧНОЇ МЕРЕЖІ - Буткевич , О.Ф.; Чиженко , О.І.; Трач , І.В. (Інститут електродинаміки Національної академії наук України, 2020)
The scheme of the device’s technical solution for direct starting of an induction motor (IM) from a “weak” electric network (EN). Such device reduces the negative influence of the start-up current of the IM on the EN mode's parameters. It is shown that the proposed solution has advantages over known solutions of the same purpose. References 9, figures 4, table.